Alternative Silvicultural Approaches to Managing Jack Pine Plantations for Endangered Species Habitat and Forest Products. Issue 2 (3rd December 2019) - Gadoth-Goodman, Daphna; Rothstein, David E
Abstract: Since the early 1980s, ca 1, 550 hectares (3, 800 ac) of high-density jack pine ( Pinus banksiana ) plantations have been established annually in northern Lower Michigan to serve as habitat for the federally endangered Kirtland's warbler (KW; Setophaga kirtlandii ). Because these plantations do not appear capable of producing merchantable sawlogs by their planned 50-year harvest age, we investigated the potential to implement reduced rotation lengths in these stands to produce biomass and/or pulpwood. We used space-for-time substitution to assess biomass and volume accrual over time, using our own locally derived allometric biomass equations. The predicted optimal rotation age for biomass was 20 years, and the predicted optimal rotation age for pulpwood volume was 28 years. We compared the total land area required for management under these rotation scenarios to continue establishing 1, 550 hectares (3, 800 ac) of KW habitat annually. Management on the current 50-year cycle requires ca 77, 500 hectares (191, 500 ac). Management for pulpwood would reduce this to ca 43, 400 hectares (107, 250 ac), and management for biomass would require ca 31, 000 hectares (76, 600 ac). Our results suggest that rotation lengths in these plantations could be substantially reduced, allowing for reductions in the total land area dedicated to warbler habitat, allowing for diversification of management at the landscape scale.